CHOROIDAL VASCULAR HYPERPERMEABILITY AS A PREDICTOR OF TREATMENT RESPONSE FOR POLYPOIDAL CHOROIDAL VASCULOPATHY. Issue 8 (August 2018) - Yanagi, Yasuo; Ting, Daniel S. W.; Ng, Wei Yan; Lee, Shu Yen; Mathur, Ranjana; Chan, Choi Mun; Yeo, Ian; Wong, Tien Yin; Cheung, Gemmy Chui Ming
Abstract : Purpose: To investigate the influence of choroidal vascular hyperpermeability (CVH) and choroidal thickness on treatment outcomes in eyes with polypoidal choroidal vasculopathy (PCV) undergoing anti–vascular endothelial growth factor monotherapy or combination therapy of photodynamic therapy and anti–vascular endothelial growth factor injections. Methods: The authors performed a prospective, observational cohort study involving 72 eyes of 72 patients with polypoidal choroidal vasculopathy (mean age 68.6 years, 51% men) treated with either monotherapy (n = 41) or combination therapy (n = 31). Each eye was imaged with color fundus photography, fluorescent angiography, indocyanine green angiography, and spectral domain optical coherence tomography. Indocyanine green angiography images were used to evaluate CVH, and spectral domain optical coherence tomography was used to measure central choroidal thickness. Changes in visual acuity over 12 months, and number of anti–vascular endothelial growth factor injections were investigated. Results: Choroidal vascular hyperpermeability was present in 31 eyes (43.1%). Visual acuity change over 12 months was numerically better in the CVH group compared with the CVH (−) group (−0.099 and −0.366 logarithm of the minimal angle of resolution unit in the CVH (−) and CVH (+) groups, respectively, multivariate P = 0.063) and significantly better in a matched pair analysis ( P = 0.033). Furthermore, in the combination therapy group, the number of injection was significantly lower in the CVH (+) group compared with the CVH (−) group (4.68 vs. 2.58 injections/year in the CVH (−) and CVH (+) groups; P = 0.0044). There was no significant relationship between treatment response and choroidal thickening. Conclusion: The presence of CVH is associated with better visual outcome in eyes with polypoidal choroidal vasculopathy and lower injection number in combination therapy. Thus, CVH, but not choroidal thickness, should be further evaluated as a potential biomarker for selecting patients for combination therapy. Abstract : The authors evaluated the influence of choroidal vascular hyperpermeability and choroidal thickness on treatment outcomes in polypoidal choroidal vasculopathy eyes undergoing anti–vascular endothelial growth factor monotherapy or combination therapy of photodynamic therapy and anti–vascular endothelial growth factor injections, and found that the presence of choroidal vascular hyperpermeability is associated with better visual outcome and lower injection number in combination therapy.